PEACE ALFALFA - McKENZIE, J. S.; PANKIW, P.; SIEMENS, B. (Canadian Journal of Plant Science, 1981)
Peace is a landrace cultivar developed at the Agriculture Canada Experimental Farm, Fort Vermilion, Alberta. It is a hardy, long-lived alfalfa, with good persistence and rapid regrowth after cutting in northern regions. It was granted license No. 2022 in Canada, in April 1980.